2015
DOI: 10.1016/j.toxicon.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Does toxic defence in Nycticebus spp. relate to ectoparasites? The lethal effects of slow loris venom on arthropods

Abstract: The venom produced by slow lorises (Nycticebus spp.) is toxic both intra- and inter-specifically. In this study we assessed the ecoparasite repellent properties of their venom. We tested venom from two Indonesian slow loris species: Nycticebus javanicus and Nycticebus coucang. Arthropods directly exposed to brachial gland secretions mixed with saliva from both species were immediately impaired or exhibited reduced activity (76%), and often died as a result (61%). We found no significant difference in the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…For an avian predator, preying on venomous animals is potentially dangerous. In experimental settings slow lorises venom injected in mice (Alterman 1995) or applied to arachnids (Grow et al 2015) is fatal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an avian predator, preying on venomous animals is potentially dangerous. In experimental settings slow lorises venom injected in mice (Alterman 1995) or applied to arachnids (Grow et al 2015) is fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Slow lorises are venomous, i.e. they can inject a substance comprised of saliva and brachial gland oil, with grooves in the powerful front teeth acting as accelerators pushing the venom upwards, allowing slow lorises to kill rodents, various arthropods, other slow lorises, or humans (Alterman 1995;Madani and Nekaris 2014;Grow et al 2015). that potentially warn off predators (Caro 2013), but they also exhibit a suite of characters, including visual (serpentine locomotion and dorsal striping) and auditory components (snake-like vocalizations), which are postulated to mimic cobras Naja spp.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Rode-Margono et al (2015), serangga dan artropoda diperkirakan dapat menjadi sumber utama pembentukan senyawa racun yang ada pada kukang. Racun tersebut pada umumnya digunakan untuk mempertahankan diri dari ancaman dan membersihkan tubuh dari ektoparasit (Grow et al, 2015;Nekaris & Starr, 2015). Kukang betina dapat saja memanfaatkan racun tersebut untuk membersihkan anaknya atau pasangannya sebagai bentuk perilaku sosial.…”
Section: Jenis Pohon Pakanunclassified
“…He suggested that the toxic proteins in the BGE must be activated by enzymes in the saliva. Grow et al [ 58 ] showed that BGE and saliva combined was also lethal to arthropods. This two-stage venom is unique in the animal kingdom.…”
Section: The Venom System and Its Functions In Mammalsmentioning
confidence: 99%